Treatment response evaluation in an ex vivo model of E. coli-infected central venous catheter system - Huo, Zihe; Légeret, Corinne; Holland-Cunz, Stefan G.; Gros, Stephanie J. (Frontiers in Pediatrics, 2025)
IntroductionDespite all precautions, central line-associated bloodstream infections (CLABSI) are inevitable, especially in children. Different treatment strategies exist for those situations. This study aims to compare the different treatment strategies.MethodsIn this study, central venous catheters (CVC, Broviac single lumen) were contaminated with E. coli in vitro. Different treatments (70% ethanol, ceftriaxone, TauroLock) were applied, and the effect was measured by isothermal microcalorimetry.ResultsA rapid decrease in heat release corresponds to a rapid decrease in the number of living bacteria. Ceftriaxone had the quickest effect followed by ethanol in combination with ceftriaxone, ethanol, and TauroLock.DiscussionAntibiotics must be based on patient risk factors, the severity of infection, and local resistance pattern; therefore, it is difficult to publish general guidelines applying to all children. In this in vitro study, ceftriaxone demonstrated the most the highest efficacy on the bacteria. Taurolidine locks are recommended for preventing CLABSI, but no data are available in regards using it for treatment. In this setting, it was efficient, as was ethanol. However, the bacteria used in this study, have not been exposed to antibiotics before—this is most likely in contrast to patients, who have a central venous catheter.ConclusionUnder in vitro conditions, systemic ceftriaxone is the most efficient and fastest treatment for an E. coli-infected CVC. Elimination of bacteria was also reached with 70% ethanol and TauroLock, but it needed more time.